RDoC, DSM, and the reflex physiology of fear: A bio-dimensional analysis of the anxiety disorders spectrum - Lang, Peter J. (Psychophysiology, 2016)
Evidence is presented supporting a dimension of defensive reactivity that varies across the anxiety disorder spectrum and is defined by physiological responses during threat-imagery challenges that covary with objective measures of psychopathology. Previous imagery studies of anxiety disorders are reviewed, highlighting that, regardless of contemporary diagnostic convention, reliable psychophysiological patterns emerge for patients diagnosed with circumscribed fear compared to those diagnosed with pervasive anxious-misery disorders. Based on the heuristic outlined by the Research Domain Criteria (RDoC) initiative, an exploratory transdiagnostic analysis is presented, based on a sample of 425 treatment-seeking patients from across the spectrum of DSM-IV anxiety diagnoses. Using a composite index of startle reflex and heart rate reactivity during idiographic-fear imagery for each patient, a defensive dimension was defined by ranking patients from most defensively reactive to least reactive and then creating five groups of equivalent size (quintile; N = 85). Subsequent analyses showed significant, parallel trends of diminishing reactivity in both electrodermal and facial EMG reactions across this defensive dimension. Negative affectivity, defined by questionnaire, and extent of functional interference, however, showed consistent, inverse trends with defensive reactivity -- as reports of distress increased, defensive reactivity was increasingly attenuated. Notably, representatives of each principal diagnosis appeared in each quintile, underscoring the reality of pronounced within-diagnosis heterogeneity in defensive reactivity. In concluding, we describe our new RDoC research project, focusing on the assessment of brain circuit function as it determines hypo/hyper reactivity to challenge—somatic and autonomic—and may relate to patients’ stress history and genetic inheritance.